Pengaruh Gaya Kepemimpinan Transformasional Terhadap Komitmen Organisasional - Paulus Umbu Lede; Katrina P Daido; Oktavianus Bili; Yunita Ngongo; Marlince Mesa (Asosiasi Riset Ilmu Teknik Indonesia, 2024)
Leaders fungtion to guide, direct, mentor, build work motivation, drive the organization, establish good communication, cary out regular supervision, and direct their subordinatis to the targets they want to achieve. In this regard, it is the obligation of every leader tomotivatie his suberdinates to work better, the leadership role is also a way that a person has to influance a group of people or subordinates to work together and make efforts with enthusiasm and confidence to achive the goals that have been set. The success of an organization, both as a whole and as a group whitin a particular organization, really depends on the effectiveness of leadership to increase employe motivation or enthusiasm for their duties and responsibilities.